INTERNATIONAL AND DOMESTIC EXPERIENCE IN ENSURING ENERGY INDEPENDENCE OF RURAL AREAS - BILOKINNA, Ilona; OKHOTA, Yuliia; CHIKOV, Illia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Energy independence is one of the key components of sustainable development, especially for rural areas, where access to centralized energy sources is often limited. The problem of providing rural areas with electricity and heat requires the implementation of innovative solutions that reduce dependence on traditional fossil resources. Many countries around the world already have successful experience in transitioning to renewable energy sources (RES) to support energy independence at the local level. Ukraine should adopt the best practices of other countries, since in conditions of martial law, energy independence of rural areas plays an important role. The article highlights the current problem of ensuring energy independence of rural areas in the context of global trends and Ukrainian realities. The authors analyze the international experience of using renewable energy sources (RES) in rural areas and highlight the key factors of successful projects. In particular, the following aspects are considered: technological innovations: the use of solar panels, wind turbines, bioenergy and microgrids; economic models: state support, cooperatives, energy communities; social impact: improvement of quality of life, creation of jobs, development of local communities; ecological advantages: reduction of greenhouse gas emissions, preservation of the environment. Particular attention is paid to the Ukrainian experience and state policy in the field of energy efficiency and renewable energy development. The authors analyze existing support programs and provide examples of successful projects. The conclusions of the article emphasize the importance of energy independence for rural areas and offer recommendations for the further development of this direction in Ukraine. The authors emphasize the need for an integrated approach that includes technological innovation, economic support and active participation of local communities.